White spot development, incubation and hatching success of leatherback turtle (Dermochelys coriacea) eggs from Rantau Abang, Malaysia - Chan, Eng Heng (American Society of Ichthyologists and Herpetologists, 1989)
White spots developed after 4-5 d of incubation in fertile eggs of the leatherback turtle, Dermochelys coriacea from Rantau Abang, Malaysia. Hatch rates of eggs handled during the first 5 d of incubation and after the appearance of the white spot were not impaired if care was exercised in handling to prevent horizontal and vertical rotation of eggs. Selection of fertile eggs for hatchery work based on the development of the white spot appears promising. Hatch rates in eggs incubated in the beach hatchery were generally lower than for eggs incubated in styrofoam boxes kept indoors. Incubation times in the beach hatchery ranged from 55-59 d, while in the styrofoam boxes it ranged from 63-82 d.